PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VD SD NEGERI 59 SEBANGAR - Sunarto, Satyo; Hamizi, Hamizi; Erlisnawati, Erlisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is backgrounded to back by its low of result study class student IPA VD SDN 59 sebangar. From 34 student only 15 student who reach completing with 44% and 19 the other student (56%) don't reach completing with average class 63,97. Aim from research this is to improve result study student of class IVD SDN 59 Sebangar with model implement Type Cooperative Studying Student Teams Achievement Division (STAD). This research is the class action research that be done in two cycles, research result to cycle first to be got as big as classical completing 88,23%, activity of teacher be to good category that is average activity of teacher 62,5% to meeting first and 75% to meeting second also activity of student be to good category that is 66,7% to meeting first and 75% to meeting second. To cycle second completings study as big as classical 100%, activity of teacher be to category very good that is 91,6% to meeting first and 95,8% to meeting second, also activity of student be to category very good that is 91,6% to meeting first and 95,8% to meeting second. with to be applied the cooperative studying model STAD's type can to improve result study student to lesson IPA in class VD SDN 59 Sebangar.Key Words : Cooperative Studying Model STAD's Learning,Science Studies Student`s Achievement (IPA)